A study of internal lighting comfortability at lecture room - Azmeen Aida, Azizul Hamid (2010)
Good lighting is very important for a classroom. A good design of building opening and building orientation can significantly produce good natural air ventilation and optimum usage of sunlight in the building where large energy savings can be achieved. The objectives of this study are to identify the lighting access in the class room and to determine the comfortness of optimum natural air ventilation and internal lighting of the room. Questionnaires were distributed to the students of Universiti Malaysia Pahang that use the class provided at Block X, Block Y and Block Z of Universiti Malaysia Pahang. The questionnaires allow the respondents to evaluate the lighting and ventilation condition of the room. The data from the questionnaires were analyzed in percentage. Most of the respondent thinks that the lighting in the room is somewhat satisfying with 62 percent and only 4 percent says that it is very dissatisfied. Finally, the study will be emphasizing on whether the façade of a building effect the movement of user in the building. It can be concluded that not all occupant of the building are satisfied with the condition of the building, many comments and suggestion are received in order to improve the condition of the building. The comfortability of the building can be improves with a more detail further research.